COMPARATIVE ANALYSIS OF STOCK PORTFOLIOS PERFORMANCE IN INDONESIA, MALAYSIA, AND SINGAPORE - Siti Epa Hardiyanti; Ika Utami Widyaningsih (PT Larva Wijaya Penerbit, 2026)
This study compares the performance of stock portfolios in Indonesia, Malaysia, and Singapore over the period 2021–2025. The objective is to evaluate and compare portfolio returns, risk levels, and risk-adjusted performance across the three capital markets. Using a quantitative approach and secondary stock market data, country-specific portfolios are constructed based on selected blue-chip stocks and evaluated using equally weighted portfolio techniques. Portfolio performance is assessed through mean return, standard deviation, beta, Sharpe Ratio, Treynor Ratio, and Jensen’s Alpha. The analysis provides insights into differences in portfolio performance among the three markets and examines the extent to which risk is compensated by return. The findings are expected to contribute to the portfolio management literature and provide practical guidance for investors seeking diversification opportunities within Southeast Asian equity markets.